Anomalous refraction of self assembled gold nanowires studied by the generalized Snell's law - Belardini, Alessandro; Leahu, Grigore; Larciprete, Maria Cristina; Centini, Marco; Sibilia, Concita; Martella, C.; Giordano, M.; Chiappe, D.; Buatier de Mongeot, Francesco (Photonics Letters of Poland, 2013)
The generalized Snell's law of refraction was introduce by F. Capasso in 2011. One consequence of the law is that resonant metallic nanostructures at the interface between two dielectrics can bent the light in a controlled way. Alternatively, by measuring the bent of a beam of light induced by a nanopatterned metallic surface it is possible to retrieve information on the surface morphology. Here we show that deviation measurements of the light passing through curved metallic nanowires deposited on a glass slide gives information on the morphology only when the resonance is excited. Full Text: PDF References N. Yu, P. Genevet, M.A. Kats, F. Aieta, J.-P. Tetienne, F. Capasso, Z. Gaburro, "Light Propagation with Phase Discontinuities: Generalized Laws of Reflection and Refraction", Science 334, 333 (2011). CrossRef X. Ni, N.K. Emani, A.V. Kildishev, A. Boltasseva, V.M. Shalaev, "Broadband Light Bending with Plasmonic Nanoantennas", Science 335, 427 (2012). CrossRef N. Engheta, "Antenna-Guided Light", Science 334, 317 (2011). CrossRef F. Aieta, P. Genevet, M.A. Kats, N. Yu, R. Blanchard, Z. Gaburro, F. Capasso, "Aberration-Free Ultrathin Flat Lenses and Axicons at Telecom Wavelengths Based on Plasmonic Metasurfaces", Nano Lett. 12, 4932 (2012). CrossRef A. Belardini, F. Pannone, G. Leahu, M.C. Larciprete, M. Centini, C. Sibilia, C. Martella, M. Giordano, D. Chiappe, F. Buatier de Mongeot, "Evidence of anomalous refraction of self-assembled curved gold nanowires", Appl. Phys. Lett. 100, 251109 (2012). CrossRef A. Belardini, F. Pannone, G. Leahu, M.C. Larciprete, M. Centini, C. Sibilia, C. Martella, M. Giordano, D. Chiappe, F. Buatier de Mongeot, "Asymmetric transmission and anomalous refraction in metal nanowires metasurface", J. Europ. Opt. Soc. Rap. Public. 7, 12051 (2012). CrossRef A. Belardini, C. Sibilia, Optoelectron. Adv. Mater. ? Rapid Commun. 7, 184 (2013). DirectLink A. Sinibaldi, N. Danz, E. Descrovi, P. Munzert, U. Schulz, F. Sonntagd, L. Dominici, F. Michelotti, "Direct comparison of the performance of Bloch surface wave and surface plasmon polariton sensors", Sensors and Actuators B 174, 292?298 (2012). CrossRef A. Belardini, A. Bosco, G. Leahu, M. Centini, E. Fazio, C. Sibilia, M. Bertolotti, S. Zhukovsky, S.V. Gaponenko, "Femtosecond pulses chirping compensation by using one-dimensional compact multiple-defect photonic crystals", Appl. Phys. Lett. 89, 031111 (2006). CrossRef A. Belardini, M.C. Larciprete, M. Centini, E. Fazio, C. Sibilia, D. Chiappe, C. Martella, A. Toma, M. Giordano, F. Buatier de Mongeot, "Circular Dichroism in the Optical Second-Harmonic Emission of Curved Gold Metal Nanowires", Phys. Rev. Lett. 107, 257401 (2011). CrossRef A. Belardini, M.C. Larciprete, M. Centini, E. Fazio, C. Sibilia, M. Bertolotti, A. Toma, D. Chiappe, F. Buatier de Mongeot, "Tailored second harmonic generation from self-organized metal nano-wires arrays", Opt. Expr. 17, 3603 (2009). CrossRef